Ionospheric response to major storm of 17th March 2015 using multi-instrument data over low latitude station Kolhapur (16.8°N, 74.2°E, 10.6°dip. Lat.). Issue 3 (1st August 2018) - Ghodpage, R.N.; Patil, P.T.; Gurav, O.B.; Gurubaran, S.; Sharma, A.K.
Abstract: The optical observations of ionospheric and mesospheric OI 630.0 nm, OI 557.7 nm along with OH emission carried out from low latitude Indian station, Kolhapur (16.8°N, 74.2°E) using CCD based all-sky camera system. The features of night airglow variations observed during the period of a strong geomagnetic storm, which commenced on March 17, 2015, at ∼04:30 UT (10:00 IST (Indian Standard Time = UT + 5.5 h)). Dst of ∼−222 nT was seen in this storm suggest that this is among the strongest. The OI 630.0 nm images on 16, 17 and 18 March show the development of Equatorial Plasma Bubbles (EPBs) and bright intensity regions in OI 630.0 nm emission. Generally, EPBs move from west to east direction but it moved in reverse direction on the strong magnetically disturbed night. The EPBs drift velocity was less by ∼100 m/s than the velocity measured on magnetically quite night 16–17 March 2015. The bright intensity regions are also observed in OI 557.7 nm airglow, but there is no intensity enhancement seen in OH emission. It is also observed that the OI 630.0 nm intensity variation well matches with the GPS VTEC variation for PRN-2. The reversal in EPBs drift velocity and the nightglow intensity variations due to the strong magnetic storm are discussed.